Water Resistance Ability and Mechanical Strength of Eco-Friendly Particleboard Made from Bamboo Waste and Maltodextrin-Based Adhesive - Greitta Kusuma Dewi; Ragil Widyorini; Erlina Nurul Aini; Yunida Syafriani Lubis (Drvna Industrija)
Bamboo waste from the handicraft and furniture industry is an excellent source of lignocellulose with significant potential for use as raw material in particleboard production. The bamboo particleboard, when paired with a natural adhesive such as maltodextrin-based adhesive, potentially provides an eco-friendly waste management solution, aligning with Sustainable Development Goals (SDGs) 12 and 13. The optimal manufacturing conditions for maltodextrin/ammonium dihydrogen phosphate (M/ADP)-based particleboard are still under investigation. In this study, our aim was to assess the quality of bamboo-M/ADP particleboard, focusing on its water resistance and mechanical properties, the crucial factors in determining particleboard quality. Various M/ADP ratios were used, namely 100/0, 90/10, and 80/20 wt%. The pressing conditions used a temperature of 200 °C at 3 MPa, with pressing times of 1, 3, 5, 7.5, and 10 minutes. The results showed that particleboard with a M/ADP ratio of 90/10 and 80/20 wt% demonstrated satisfactory water resistance, as supported by the results of thickness swelling and aging evaluations. Overall, the M/ADP 80/20 wt% at 10 minutes of pressing time exhibited optimal particleboard properties, i.e., thickness swelling 5.08 %, thickness change after aging treatment 5.29 %, water absorption 38.47 %, surface roughness 8.92 μm, internal bonding strength 0.21 N/mm², modulus of rupture 4.8 MPa, modulus of elasticity 1.72 GPa, and brittleness 41.7 %.